(untitled) (Research, Society and Development, 2023)
The purpose of this paper is to discuss the adoption process as a possibility in the foster family service, as well as to present the importance of affiliation and belonging in the development of the subjective self of the children and adolescents participating in this service. It also seeks to understand how the process of removing children from their families of origin takes place and how they are reintegrated when this is still possible. The methodology used to carry out this work was a systematic bibliographical review in order to better identify the results found and thus use concepts from psychology to analyze all the family contexts of these individuals, in addition to demonstrating the importance of monitoring before and after the adoption is carried out. In the end, the aim is to gain a better understanding and give greater visibility to the subject by providing information to people who are interested in the subject, which is of the utmost importance today.